The influence of percentage replacement on the aggregate and concrete properties from commercially produced coarse recycled concrete aggregate - Immelman, Derick Wade (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.